2007
DOI: 10.1155/2007/531739
|View full text |Cite
|
Sign up to set email alerts
|

Operational Modal Analysis for Estimating the Dynamic Properties of a Stadium Structure during a Football Game

Abstract: During a football game, the ambient vibrations at the roof of a football stadium were recorded. A very large data set consisting of 4 hours of data, sampled at 80 Hz, is available. By a data reduction procedure, the complete data set could be analysed at once in a very short time. The data set was also split in shorter segments corresponding to certain events before, during and after the game to investigate the influence of varying operational conditions on the dynamic properties.As the structural vibrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…Estimating the auto and the cross-power spectra using the periodogram approach [17,18]; 3. Estimating the modal parameters of the drivetrain modes in the frequency band of interest using the polyreference Least-Squares Complex Frequency-domain (pLSCF) estimator [19][20][21]; 4. Automatic tracking of the modes of interest based on the Modal Assurance Criterion (MAC), frequency value, and damping ratio value.…”
Section: Automatic Tracking Of Drivetrain Modes: High Frequency-band mentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating the auto and the cross-power spectra using the periodogram approach [17,18]; 3. Estimating the modal parameters of the drivetrain modes in the frequency band of interest using the polyreference Least-Squares Complex Frequency-domain (pLSCF) estimator [19][20][21]; 4. Automatic tracking of the modes of interest based on the Modal Assurance Criterion (MAC), frequency value, and damping ratio value.…”
Section: Automatic Tracking Of Drivetrain Modes: High Frequency-band mentioning
confidence: 99%
“…An n th order right matrix-fraction model yields nN re f poles. For a displacement output quantity, the full power spectrum can be written as a function of the modal parameters (pole λ i ∈ C, modal operational reference factors V i ∈ C N re f ×1 , mode shapes ψ i ∈ C N o ×1 ) as [21,22]:…”
Section: The Polyreference Least-squares Complex Frequency-domain (Plmentioning
confidence: 99%
See 1 more Smart Citation
“…OMA allows the investigator to collect modes that are relevant to the operation of the machine. A review of OMA methods can be found in [10] and some recent developments are discussed in [11]. The original application of OMA (although that name was not in use at that time) to wind turbines can be found in [12] [13].…”
Section: Full-scale Modal Wind Turbine Tests: Comparing Shaker Excitamentioning
confidence: 99%
“…Moreover, the use of an exponential window in the pre-processing stage is an excellent "de-noising" tool that could not be applied here. More details about the advantages of the use of half spectra (or correlograms) in comparison with the more classical spectra (or periodograms) can be found in [11]. In the near future, more extensive operational time-domain data will be acquired.…”
Section: Operational Modal Analysis -Wind Excitationmentioning
confidence: 99%